(untitled) (Revista de Estudos da Linguagem, 2007)
This work argues about the variation in the behavior of the individualin a probabilistic approach in phonology, analyzing the applicabilityof some phonological phenomena between the individuals evaluatedhere. We argue in accordance to the theoretical referencial that weadopt – Usage Based Phonology (BYBEE, 2001), Exemplars Model(PIERREHUMBERT, 2001) and Probabilistic Linguistics (BOD; HAY;JANNEDY, 2003) – that the organization of the linguistic componentis based on multiple representations, linked in nets and regulated byprobabilistic criteria. Amongst others, we make an analysis of thewords in study and show that words related to a specific phenomenoncan have different levels of accomplishment.